Instagram Content Management Strategy In Building Customer Engagement (Study on Mahar Agung Organizer) - Farahlia Megandita; Syaifuddin Zuhri (International Journal of Social, Economic, and Business, 2026)
This research explores how Instagram content is managed to foster customer engagement in Mahar Agung Organizer, a business operating in the wedding service sector. In today’s digital environment, social media functions not only as a promotional tool but also as a platform that enables brands to maintain continuous interaction and build meaningful relationships with their audiences.A qualitative method was applied to gain deeper insights into the phenomenon. Data were gathered through interviews, direct observation of the Instagram account, and documentation of published content. The analysis process followed an interactive model involving data condensation, data presentation, and interpretation.The results indicate that content management is carried out in a structured manner, starting from planning, organizing content into thematic pillars, and distributing content using various Instagram features. Content formats such as storytelling, testimonials, and real event documentation contribute significantly to increasing audience involvement.